Construction and validity of educational technology in audiovisual media on premature newborn care - Marcelo Victor Freitas Nascimento; Willyane de Andrade Alvarenga; Marcia Teles de Oliveira Gouveia; Herla Maria Furtado Jorge; Marianne Rocha Duarte de Carvalho; Jackeline Vieira Amaral; Silvana Santiago da Rocha (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to construct and validate an educational video storyboard about care for premature newborns at home. Methods: a methodological study, with the construction of an educational video storyboard, validated with 14 judges. Content was selected from scoping review. For data collection, a validated instrument was used. The criterion for validity was agreement greater than 80%, analyzed using the Content Validity Index. Results: the storyboard construction was guided by the Cognitive Theory of Multimedia Learning theoretical framework. Construction and validity took place from May to December 2020. The storyboard's final version lasted 10 minutes, and was validated in terms of objective, structure, presentation and relevance, with a Content Validity Index of 0.9. Conclusions: the storyboard of the educational video proved to be valid and adequate for health promotion in developing care for premature newborns at home.